2019
DOI: 10.1002/jat.3797
|View full text |Cite
|
Sign up to set email alerts
|

Rebaudioside A administration prevents experimental liver fibrosis: an in vivo and in vitro study of the mechanisms of action involved

Abstract: Rebaudioside A (Reb A) is a diterpenoid isolated from the leaves of Stevia rebaudiana (Bertoni) that has been shown to possess pharmacological activity, including antiinflammatory and antioxidant properties. However, the ability of Reb A to prevent liver injury has not been evaluated. Therefore, we aimed to study the potential of Reb A (20 mg/kg; two times daily intraperitoneally) to prevent liver injury induced by thioacetamide (TAA) administration (200 mg/kg; three times per week intraperitoneally). In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…by activating nuclear factor erythroid 2-related factor 2 (Nrf2) response, an important transcription factor that can avert inflammation. Similar findings were reported by a recent study by Casas-Grajales in 2019, in which they demonstrated that rebaudioside A preserved expression of Nrf2 as well as downregulated/prevented the expression of pro-inflammatory pathway and genes such as NF-κB, TGF-β1, Smad7 and MMP-13 protein (Casas-Grajales et al 2019a, 2019b.…”
Section: More Than Just Sweetener: Anti-inflammatory Activity Of S Rsupporting
confidence: 90%
See 1 more Smart Citation
“…by activating nuclear factor erythroid 2-related factor 2 (Nrf2) response, an important transcription factor that can avert inflammation. Similar findings were reported by a recent study by Casas-Grajales in 2019, in which they demonstrated that rebaudioside A preserved expression of Nrf2 as well as downregulated/prevented the expression of pro-inflammatory pathway and genes such as NF-κB, TGF-β1, Smad7 and MMP-13 protein (Casas-Grajales et al 2019a, 2019b.…”
Section: More Than Just Sweetener: Anti-inflammatory Activity Of S Rsupporting
confidence: 90%
“…It has been speculated that the activators of Nrf2 can hinder IKK/IκB phosphorylation and p65 NF-κB subunit nuclear translocation, and then preventing NF-κB signaling pathway. Based on the proposed theory, stevioside may possibly prevent inflammation (a) via direct actions on NF-κB signaling pathway which then inhibiting the production of pro-inflammatory cytokines, and/or (b) via activating Nrf2 antioxidant response which then inhibits NF-κB signaling pathway (Bunprajun et al 2012;Yingkun et al 2013;Garcia-Arroyo et al 2016;Ramos-Tovar et al 2018a, 2018bCasas-Grajales et al 2019a, 2019b.…”
Section: More Than Just Sweetener: Anti-inflammatory Activity Of S Rmentioning
confidence: 99%
“…Several studies have been performed to investigate the effects of various antioxidants on different models of liver damage and have shown the causative role of ROS in the profibrogenic process. In models of bile duct ligation-, CCl 4 -, and thioacetamide chronic intoxication-induced fibrosis in rodents and in vitro studies, several compounds with direct or indirect antioxidant activity have been shown to prevent or reverse the accumulation of extracellular matrix (ECM) proteins (fibrotic tissue) within the hepatic parenchyma or the production of profibrogenic genes or proteins [59][60][61][62][63][64][65][66][67][68][69][70][71][72]. One of the most studied phytodrugs with important antioxidant properties is silibinin, the main active constituent of silymarin [73].…”
Section: Attenuating Oxidative Stress Produces An Antifibrotic Effectmentioning
confidence: 99%
“…Numerous studies suggested that high-intensity sodium saccharin contributed adverse biological, even toxicological, effects on reproductive systems (19,(32)(33)(34)(35). Conversely, a certain intensity of rebaudioside A represented positive biological functions (36)(37)(38). A study showed that natural sweeteners exerted their sweet taste by specifically binding to sweet taste receptors (39).…”
Section: Discussionmentioning
confidence: 99%